Callus of American ginseng (Panax quinquefolius) as a source of ginsenosides – medicinal secondary metabolites - Kochan, Ewa; Chmiel, Aleksander (Biological Letters, 2014)
:Asian ginseng (Panax ginseng) and American ginseng (P. quinquefolius) are valuable medicinal herbs whose roots have been used for ages in traditional medicine in China and North America as vitalizing and stimulating agents. The roots are obtained mainly from field cultivation, which is a slow (5-7 years long), laborious, and troublesome process; so in vitro methods started to be used to produce ginseng biomass. In our study, non-organogenic callus of P. quinquefolius synthesized the same active substances like field roots, for more than 6 years. The ginsenosides are derivatives of protopanaxadiol (Rb1, Rb2, Rc, Rd) or protopanaxatriol (Rg1, Re). The synthesis of Rg1 and Re metabolites is preferred in calli cultured in the dark and with ageing of culture.